Upaya Meningkatkan Hasil Belajar IPA (Fisika) Dengan Model Pembelajaran Cooperative Script di Kelas VII SMP Negeri 17 Halmahera Selatan - Haryati Mahyudin (Peneliti.net, 2022)
This research is a descriptive qualitative research with research subjects are class VIII students, with the teacher as the data source. Research data collection techniques were carried out using observation sheets carried out by learning models and test questions. The data obtained were analyzed qualitatively. The results showed that the learning outcomes of students in cycle I showed an average class value of 68 with students who passed, namely 15 out of 29 the number of students in class VII so that the percentage obtained was 52%, because students were less active in learning so that the scores obtained by students still did not reach the KKM, namely 75. In the improvement of cycle II, students began to get used to using the cooperative script learning model so that student learning outcomes increased. This showed an increase in physics learning outcomes (IPA).